Transparent alumina ceramics: Effect of standard and plasma generated stabilizing approaches in colloidal processing - Drdlíková, Katarina; Maca, Karel; Sláma, Martin; Drdlík, Daniel (Wiley, 2019)
The study is focused on an optimization of the slipcasting process used for the fabrication of the transparent/translucent alumina ceramics; more precisely, on specifying the most appropriate way to stabilize the cast alumina suspensions. An innovative method of the particles’ stabilization by plasma treatment was compared with the classical electrostatic and the most frequently used electrosteric approach. Properties of green bodies (pore size distribution, density) and sintered samples (density, mean grain size, real inline transmittance) were measured in term to evaluate the impact of the individual stabilization mechanism on the final properties of the transparent/translucent ceramics. The results showed that all tested approaches enable the preparation of the transparent/translucent alumina ceramics by Hot Isostatic Pressing. Ceramics prepared from the plasma treated as well as the electrostatically stabilized powders exhibited narrower pore size distribution, higher density, and lower mean grain size in comparison to ceramics fabricated from only electrosterically stabilized powders. Despite these promising properties the plasmatreated samples resulted in an unexpectedly low RIT of 36% caused by the presence of thin cracks. However, the electrostatically stabilized samples achieved the highest RIT value of 57%.

The study is focused on an optimization of the slipcasting process used for the fabrication of the transparent/translucent alumina ceramics; more precisely, on specifying the most appropriate way to stabilize the cast alumina suspensions. An innovative method of the particles’ stabilization by plasma treatment was compared with the classical electrostatic and the most frequently used electrosteric approach. Properties of green bodies (pore size distribution, density) and sintered samples (density, mean grain size, real inline transmittance) were measured in term to evaluate the impact of the individual stabilization mechanism on the final properties of the transparent/translucent ceramics. The results showed that all tested approaches enable the preparation of the transparent/translucent alumina ceramics by Hot Isostatic Pressing. Ceramics prepared from the plasma treated as well as the electrostatically stabilized powders exhibited narrower pore size distribution, higher density, and lower mean grain size in comparison to ceramics fabricated from only electrosterically stabilized powders. Despite these promising properties the plasmatreated samples resulted in an unexpectedly low RIT of 36% caused by the presence of thin cracks. However, the electrostatically stabilized samples achieved the highest RIT value of 57%.
Transparent alumina ceramics: Effect of standard and plasma generated stabilizing approaches in colloidal processing
Keywords: alumina; dispersants/dispersion; transparent ceramics; alumina; dispersants/dispersion; transparent ceramics